Intrinsic Reason for the Morphology Dependence of Luminescent Behavior: A Case Study with GdVO4:Eu3+ Nanocrystals. Issue 35 (5th November 2013) - Yang, Liusai; Li, Guangshe; Zhao, Minglei; Zheng, Jing; Luo, Dong; Zheng, Yunlong; Li, Liping
Abstract: Rare‐earth orthovanadates, a kind of prototypical host, have received extensive attentions owing to their important applications. Although there has been great progress in the control of morphologies and optimzation of properties, the intrinsic reasons for the morphology dependence of their luminescence are still unclear. In this work, we chose GdVO4 :Eu 3+ as a model compound to study. By varying the surfactant dose involved under mild hydrothermal conditions, several distinct morphologies, such as nanorods, nanowafers, nanoparticles, and snowballs were prepared. Depending on the morphologies and residual surfactant content, surface cationic nonstoichiometry and defects, especially for unstable VO4 groups, were demonstrated to exist in GdVO4 :Eu 3+ nanocrystals. The first experimental evidence for the relationship between surface defect states and luminescent emission of GdVO4 :Eu 3+ nanocrystals is presented. Abstract : Nanostructured GdVO4 :Eu 3+ particles with different morphologies, including nanorods, nanowafers, nanoparticles, and snowballs are presented for the first time to explore the relationship between surface defects and luminescent emission of GdVO4 :Eu 3+ nanocrystals.